2023
DOI: 10.1186/s40659-023-00444-3
|View full text |Cite
|
Sign up to set email alerts
|

Hyperbaric oxygen treatment increases intestinal stem cell proliferation through the mTORC1/S6K1 signaling pathway in Mus musculus

Abstract: Background Hyperbaric oxygen treatment (HBOT) has been reported to modulate the proliferation of neural and mesenchymal stem cell populations, but the molecular mechanisms underlying these effects are not completely understood. In this study, we aimed to assess HBOT somatic stem cell modulation by evaluating the role of the mTOR complex 1 (mTORC1), a key regulator of cell metabolism whose activity is modified depending on oxygen levels, as a potential mediator of HBOT in murine intestinal stem … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…While the mechanisms mediating these effects are not fully understood, several studies have identified potential pathways. Specifically, the therapeutic effects of HBOT have been found to be mediated by increased growth factor synthesis, stem cell mobilization, attenuated monocyte chemokine production, neutrophil β-actin 5-nitrosylation, and changes in inflammatory markers, which overall lead to neovascularization and improved tissue survival [11,76,77]. Changes in oxygen transport and metabolism have also been implicated as mechanistically underlying HBOT.…”
Section: Hbot Mechanism Of Actionmentioning
confidence: 99%
“…While the mechanisms mediating these effects are not fully understood, several studies have identified potential pathways. Specifically, the therapeutic effects of HBOT have been found to be mediated by increased growth factor synthesis, stem cell mobilization, attenuated monocyte chemokine production, neutrophil β-actin 5-nitrosylation, and changes in inflammatory markers, which overall lead to neovascularization and improved tissue survival [11,76,77]. Changes in oxygen transport and metabolism have also been implicated as mechanistically underlying HBOT.…”
Section: Hbot Mechanism Of Actionmentioning
confidence: 99%
“…The mobilization of stem cells is an imperative feature of wound healing as it advances through three stages: the inflammatory phase, the proliferation phase, and the remodeling phase [39]. HBOT is then shown to increase the proliferation within the intestinal stem cells of mice without adverse effects to oxidative metabolism [11,40]. HBOT was successfully completed on a patient within a tertiary care hospital of the armed forces as seen in the sequential photographs of the diabetic patient within (Figure 2) [41].…”
Section: Stem Cells and Wound Healingmentioning
confidence: 99%